ITEM ADAPTIF MENGGUNAKAN LOGIKA FUZZY MAMDANI PADA GAME BERTEMA KEBERSIHAN SUNGAI - Septian Idhi Pangestu; Hanny Haryanto; Erlin Dolphina (Universitas Raharja, 2018)
Indonesia is characterized by its biodiversity. Such biodiversityneeds to be preserved. One that needs to be taken care of is the cleanliness of the river environment frompollution, especially waste. However, the awareness of Indonesian people not to throw garbage in the river isstill lacking. It is necessary for socialization to increase public awareness. Gamecan be used for learning because it will encourage fun interaction between players and computers. In the game, itemswill appear randomly or in accordance with the configuration specified by the developer. This is less effective because if the item does not appear or the item that appears does not match the needs of players thenplayers will be difficult and tend to experience failure in completing the game. Fuzzy Mamdani method isused to determine the type of item that appears in accordance with what is currently required by the player.Input is derived from the residual health value of the player, the remaining marine health, as well as thenumber of mistakes made by the player, while the output is an item required by the player. The result makes the appearance of items more adaptive to players needs